A longitudinal study defined circulating microRNAs as reliable biomarkers for disease prognosis and progression in ALS human patients - Gabriella Dobrowolny; Julie Martone; Elisa Lepore; Irene Casola; Antonio Petrucci; Maurizio Inghilleri; Mariangela Morlando; Alessio Colantoni; Bianca Maria Scicchitano; Andrea Calvo; Giulia Bisogni; Adriano Chiò; et al. (Cell Death Discovery, 2021)
Abstract Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease associated with motor neuron degeneration, muscle atrophy and paralysis. To date, multiple panels of biomarkers have been described in ALS patients and murine models. Nevertheless, none of them has sufficient specificity and thus the molecular signature for ALS prognosis and progression remains to be elucidated. Here we overcome this limitation through a longitudinal study, analyzing serum levels of circulating miRNAs, stable molecules that are recently used as promising biomarkers for many types of human disorders, in ALS patients during the progression of the pathology. We performed next-generation sequencing (NGS) analysis and absolute RT quantification of serum samples of ALS patients and healthy controls. The expression levels of five selected miRNAs were quantitatively analyzed during disease progression in each patient and we demonstrated that high levels of miR-206, miR-133a and miR-151a-5p can predict a slower clinical decline of patient functionality. In particular, we found that miR-206 and miR-151a-5p serum levels were significantly up-regulated at the mild stage of ALS pathology, to decrease in the following moderate and severe stages, whereas the expression levels of miR-133a and miR-199a-5p remained low throughout the course of the disease, showing a diagnostic significance in moderate and severe stages for miR-133a and in mild and terminal ones for miR-199a-5p. Moreover, we found that miR-423–3p and 151a-5p were significantly downregulated respectively in mild and terminal stages of the disease. These data suggest that these miRNAs represent potential prognostic markers for ALS disease.